COMPARISON OF OPEN WITH LAPAROSCOPIC COMMON BILE DUCT EXPLORATION - Safdar, Kamran; Wattoo, Nasir Mehmood; Butt, Qasim; Yasin, Talha; Asif, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the difference in outcome of laparoscopic versus open methods for common bile duct exploration at Combined Military Hospital Rawalpindi.Study Design: Comparative study.Place and Duration of Study: Pak Emirates Military Hospital and Combined Military Hospital, Rawalpindi, from Jun 2018 to Apr 2019.Methodology: A prospective study was conducted on 60 patients who underwent bile duct exploration either open or laparoscopic, for possibly benign conditions, were included in the study. Follow-up assessment regarding all the side effects was done immediately after the procedure, at 48 hours, at time of discharge and two weeks post procedure on all the participants. Demographic profile and surgical method were compared in the groups with and without the complications by using the chi-square test and binary logistic regression.Results: Mean age of patients in our study was 45.83 ± 2.271. Bile duct leakage was the commonest complication among the target population followed by wound infection. Open method and presence of co-morbidities had a strong correlation with presence of complications among the patients undergoing bile duct exploration in our study.Conclusion: Laparoscopic method emerged as a safe technique for common bile duct exploration as compared to the open method in our patients. Special attention should be paid to patients with medical co morbidities and level of suspicion should be high in them for the post-operative complications.